(3HhQUI GdChQGb GdeGdjI (B:s (3Hjf GdfXQjI hGdJWHjb (B/s - (3GdMfGhj, eMeO UGdMs; (3GdYHO, LdGd GHQGgje s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2005)
(3CShGb GdeGd hGdChQGb GdeGdjI, CShGb GdChQGb GdeGdjI aj GdOhd GdeJbOeI, JMOjO CSYGQ GdChQGb GdeGdjI aj GdHhQUI, Shb GdChQGb GdeGdjI aj eUQ, UfGOjb GdGSJKeGQ, Jbjje COGA UfGOjb GdGSJKeGQ, eDTQGJ GdShb, bQGAI hJMdjd GdHjGfGJ GdeGdjI GdefThQI, YbhO GdeHGOdGJ, GdYbhO GdeSJbHdjIs
(3eUWdMGJ gGeI U(B.394 (3bGehS TQM GdeUWdMGJ U(B.395s
Keywords: (3GdChQGb GdeGdjIs; (3GdHhQUGJs